Data sonification artworks : a music and design investigation of multi-modal interactive installations. - Caldis, Constantina (My University, 2014)
Through three case studies this research report will explore the design and multimodal attributes of interactive installations that feature characteristics comparable to those of musical instruments. It will briefly outline and define data sonification and the five sonification techniques: Audification, Auditory Icons, Earcons, Parameter-mapping sonification and Model-based sonification. Model-based data sonification will be more closely explored, as interactivity and the incorporation of multiple modes are key elements within these types of sonifications. Pre-existing knowledge of musical instruments, their multi-modal attributes and functionality will be analyzed in relation to the case studies. The design analysis will focus on the interaction and interface design while incorporating the three modes, namely: visual guidance, real-time physical/gestural interaction, and instantaneous acoustic feedback. To conclude, this research report will demonstrate, through the case studies, that the function and design of musical instruments can be suggestive in realizing a potential way forward for digital artists and their multi-modal interactive installations.
Keywords: Computer art.; Interactive art.